Tough high-barrier functional membrane material as well as preparation method and application thereof
By introducing PDLA/PPCM Janus nanosheets into the PLLA/PPC blend, forming tamto-composite crystals, the problem of poor compatibility of the blend is solved, and its mechanical properties and barrier properties are significantly improved, and its application scope is expanded.
Patent Information
- Application Number
- CN202411991551.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-12-31
AI Technical Summary
PLA/PPC blends have poor compatibility and exhibit poor comprehensive performance. Traditional compatibilizers are inefficient and lack functionality, limiting the application range of blends.
The PDLA/PPCM Janus nanosheets were modified by using SiO2 hollow spheres as template and added to the matrix PLLA/PPC to form stereocomposite crystals to improve the capacity-enhancing efficiency and barrier properties of the blend.
It significantly improves the tensile strength, elongation at break and barrier properties of the blend, enhances the compatibility and functionality of the polymer, and is suitable for food, daily necessities, environment, agriculture or pharmaceutical fields.
Smart Images

Figure CN119775741A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of functional materials, and in particular to a tough high-barrier functional film material and a preparation method and application thereof. Background Art
[0002] With the continuous development of science and technology, the performance of single-component materials can no longer meet modern needs. Therefore, blending modification is a necessary processing strategy. However, after blending, most materials have poor compatibility and no performance improvement.
[0003] Polylactic acid (PLA) is a bio-based degradable material with high strength and good processing performance. It is one of the most successful commercial degradable materials. Polypropylene carbonate (PPC) has attracted widespread attention. It is a new type of biodegradable aliphatic polymer with good degradability, barrier properties, transparency, and non-toxicity. It is widely used in food packaging, medical devices, engineering plastics and other fields. However, PLA / PPC blends have poor compatibility and show poor overall performance. At present, traditional compatibilizers have problems such as low efficiency and lack of functionality, which limit the application scope of the blends. Summary of the invention
[0004] In view of the above problems existing in the prior art, the present invention provides a tough high barrier functional membrane material and its preparation method and application. The present invention uses SiO2 hollow spheres as templates to modify them and prepare PDLA / PPCM Janus nanosheets, which are added to the matrix PLLA / PPC to better disperse at the interface between the two phases, thereby effectively improving the volume expansion efficiency of the blend.
[0005] The technical solution of the present invention is as follows:
[0006] The first object of the present invention is to provide a tough high barrier functional film material, comprising the following raw materials in parts by weight: 60-90 parts of L-polylactic acid, 10-40 parts of polypropylene carbonate, and 0.1-3 parts of PDLA / PPCM Janus nanosheets;
[0007] PDLA / PPCM Janus nanosheets use SiO2 hollow spheres as templates, and curcumin-grafted poly(propylene carbonate) glycol (PPCM) and dextrorotatory poly(lactic acid) (PDLA) are modified on both sides of the templates, respectively.
[0008] In one embodiment of the present invention, the preparation method of PDLA / PPCM Janus nanosheets is:
[0009] (1) PPC diol reacts with lysine diisocyanate. After the reaction is completed, SiO2 hollow sphere dispersion and curcumin are added to the system to obtain SiO2 hollow spheres with PPCM grafted on the outer surface;
[0010] (2) The SiO2 hollow spheres with PPCM grafted on the outer surface are ultrasonically crushed to obtain SiO2-PPCM nanosheets, which are then reacted with a silane coupling agent and dextrorotatory polylactic acid to obtain the PDLA / PPCM Janus nanosheets.
[0011] In one embodiment of the present invention, in step (1), the molar ratio of PPC diol to lysine diisocyanate is 1:2-3.
[0012] In one embodiment of the present invention, in step (1), the reaction conditions are: PPC diol is distilled under reduced pressure at 110°C for 4-6h, then cooled to 60°C, the distilled PPC diol is dripped into lysine diisocyanate, and stirred at 50-60°C for 3-5h under nitrogen conditions; then 150-250mL of SiO2 hollow sphere dispersion (0.75 / 100, g / mL) and 2-4g of curcumin are added, the temperature is lowered to 40°C and stirred for 12-18h; then the mixture is washed with deionized water and tetrahydrofuran and centrifuged and dried to obtain SiO2 hollow spheres with PPCM grafted on the outer surface.
[0013] In one embodiment of the present invention, in step (1), the SiO2 hollow sphere dispersion is prepared by dispersing SiO2 hollow spheres in tetrahydrofuran; the concentration of the SiO2 hollow sphere dispersion is 0.5-0.75 g / 100 mL; and the particle size of the SiO2 hollow spheres is 4.5-5.5 μm.
[0014] In one embodiment of the present invention, in step (1), the mass volume ratio of PPC diol to SiO2 hollow sphere dispersion is 5-10 / 100, g / mL; the mass volume ratio of curcumin to SiO2 hollow sphere dispersion is 1-5 / 100, g / mL.
[0015] In one embodiment of the present invention, in step (1),
[0016] PPC was dropped into lysine diisocyanate, and a catalyst dibutyltin dilaurate (the addition amount was 0.01-0.05% of the mass of PPC) was added, and the reaction was stirred at 50-60°C for 3-5 hours under nitrogen conditions; then, 150-250mL of SiO2 hollow sphere dispersion and 2-4g of curcumin were added to the reaction system, and the temperature was lowered to 40°C and stirring was continued for 12-18 hours; then, the system was washed with deionized water and tetrahydrofuran and centrifuged and dried to obtain SiO2 hollow spheres with PPCM grafted on the outer surface.
[0017] In one embodiment of the present invention, in step (2), the conditions for ultrasonic disruption are: 500-600W ultrasonic treatment for 1-1.5h;
[0018] The reaction conditions are as follows: SiO2-PPCM nanosheets are dispersed in chloroform, and then a silane coupling agent KH560 is added to react at 40-50°C for 2-3.5 hours to graft epoxy groups on its surface, and then right-handed polylactic acid PDLA is added to react at 80-100°C in a three-necked flask (nitrogen) for 20-25 hours, and finally the Janus nanosheets are obtained after sufficient stirring, centrifugation, washing with chloroform, and drying.
[0019] In one embodiment of the present invention, in step (2), the silane coupling agent is KH560; the mass ratio of SiO2-PPCM nanosheets, dextrorotatory polylactic acid and silane coupling agent is 1:2-5:5-10.
[0020] In one embodiment of the present invention, in step (2), SiO2 hollow spheres with PPCM grafted on the outer surface are dispersed in anhydrous ethanol and subjected to ultrasonic treatment at 500-600W for 1-1.5h to break the hollow spheres into pieces, namely SiO2-PPCM nanosheets; then the SiO2-PPCM nanosheets are dispersed in chloroform, silane coupling agent KH560 is added and reacted at 40-50°C for 2-3.5h to graft epoxy groups on the surface thereof, and then right-handed polylactic acid PDLA is added and reacted at 80-100°C in a three-necked flask (nitrogen) for 20-25h, and finally the Janus nanosheets are obtained after sufficient stirring, centrifugation, washing with chloroform and drying.
[0021] The second object of the present invention is to provide a method for preparing the above-mentioned tough high barrier functional film material, comprising the following steps:
[0022] 60-90 parts of left-lactic acid (PLLA), 10-40 parts of polypropylene carbonate (PPC), and 0.1-3 parts of PDLA / PPCMJanus nanosheets are melt-blended and then molded to obtain the tough high-barrier functional film material.
[0023] In one embodiment of the present invention, the preparation method of the tough high barrier functional film material comprises the following specific steps:
[0024] 60-90 parts of left-lactic acid (PLLA), 10-40 parts of polypropylene carbonate (PPC), and 0.1-3 parts of PDLA / PPCMJanus nanosheets are blended at 190-200°C for 5-6 minutes, and then extruded to form a film or sheet, and then quickly cooled to below 15°C to make its crystallinity less than 10%; then the cooled film or sheet is biaxially stretched at 70-75°C using a flat film biaxial stretching process, and then heat treated at 100-110°C to obtain the tough high barrier functional film material;
[0025] or,
[0026] 60-90 parts of left-lactic acid (PLLA), 10-40 parts of polypropylene carbonate (PPC), and 0.1-3 parts of PDLA / PPCMJanus nanosheets are blended at 190-200°C for 5-6 minutes, and then formed into a tube embryo through a tube-shaped die. The tube embryo is quickly cooled to below 15°C to make its crystallinity less than 10%; the cooled tube embryo is inflated, stretched, and shaped at 70-75°C using a tube film biaxial stretching process, and then heat-treated at 100-110°C to obtain the tough high-barrier functional film material.
[0027] In one embodiment of the present invention, the stretching temperature of the flat film biaxial stretching process is 70-75° C., the heat treatment temperature is 100-110° C., the transverse stretching ratio is 4 times, and the longitudinal stretching ratio is 4 times.
[0028] In one embodiment of the present invention, the stretching temperature of the tubular film biaxial stretching process is 70-75°C, the heat treatment temperature is 100-110°C, the blowing ratio is 3 times, and the drawing ratio is 5 times.
[0029] The third object of the present invention is to provide an application of the above-mentioned tough high barrier functional film material for use in the fields of food, daily necessities, environment, agriculture or medicine.
[0030] The beneficial technical effects of the present invention are:
[0031] In the present invention, the PDLA grafted on the PDLA / PPCM Janus nanosheet and the PLLA of the matrix form stereocomposite crystals during the melt blending process, and the crystals are dispersed at the interface between the two phases, further enhancing the strength of the polymer blend.
[0032] The present invention controls the biaxial stretching conditions to orient the Janus nanosheets in the blend, greatly increasing the diffusion path of small gas molecules in the film, and the Janus nanosheets and the in-situ stereocomposite crystals formed by the PLLA of the matrix and the bridge between the PPC molecular chains form a barrier network, which has a special effect of synergistically blocking small gas molecules. Therefore, the tensile strength, elongation at break and barrier properties of the blend film are significantly improved.
[0033] In the present invention, due to the characteristics of curcumin and polylactic acid, the blend has a good anti-ultraviolet effect. In addition, by grafting curcumin, it has good dispersibility in the blend, thereby significantly improving the ammonia response ability and corruption detection ability of the blend film. Therefore, it is conducive to its application in the fields of packaging, ground film, etc.
[0034] The present invention designs a Janus structured nanosheet, and by regulating its dispersibility and biaxial stretching processes, the prepared PLLA / PPC film has both mechanical properties and high barrier properties and multifunctionality, which is conducive to the expansion of its application in the packaging field. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 Atomic force microscope images of nanosheets at different stages in Example 1;
[0036] Among them, (a) SiO2 nanosheets after ultrasonic crushing of ungrafted SiO2 (5μm) hollow spheres; (b) SiO2-PPCM nanosheets; (c) PDLA / PPCM Janus nanosheets. DETAILED DESCRIPTION
[0037] The present invention is described in detail below in conjunction with the accompanying drawings and embodiments.
[0038] Example 1
[0039] A method for preparing PDLA / PPCM Janus nanosheets comprises the following steps:
[0040] (1) 20 g of PPC was used as a diol and distilled under reduced pressure at 110° C. for 6 h, then cooled to 60° C. The distilled PPC diol was dropped into 6 g of lysine diisocyanate, and 0.005 g of dibutyltin dilaurate was added as a catalyst. The mixture was stirred at 60° C. for 3 h under nitrogen conditions. Then 200 mL (0.75 / 100, g / mL) of SiO2 hollow sphere dispersion and 3 g of curcumin were added, the mixture was cooled to 40° C. and stirred for 12 h. The mixture was then washed with deionized water and tetrahydrofuran and centrifuged to obtain SiO2 hollow spheres with PPCM grafted on the outer surface.
[0041] (2) The SiO2 hollow spheres grafted with PPCM on the outer surface were dispersed in ethanol and ultrasonically treated (500W) for 1 h to break them into pieces, thereby obtaining SiO2-PPCM nanosheets;
[0042] (3) 1 g of SiO2-PPCM nanosheets was dispersed in chloroform, and then 6 g of silane coupling agent KH560 was added to react at 40°C for 2 h to graft epoxy groups on its surface, and then 5 g of right-handed polylactic acid PDLA was added and reacted at 80°C in a three-necked flask (nitrogen) for 25 h. Finally, the Janus nanosheets were obtained after sufficient stirring, centrifugation, washing with chloroform, and drying.
[0043] Example 2
[0044] A method for preparing PDLA / PPCM Janus nanosheets comprises the following steps:
[0045] (1) 20 g of PPC was used as a diol and distilled under reduced pressure at 110° C. for 4 h, then cooled to 60° C. The distilled PPC diol was dropped into 4.5 g of lysine diisocyanate, and 0.005 g of dibutyltin dilaurate was added as a catalyst. The mixture was stirred at 50° C. for 3 h under nitrogen conditions. Then 150 mL (0.75 / 100, g / mL) of SiO2 hollow sphere dispersion and 2 g of curcumin were added, the mixture was cooled to 40° C. and stirred for 12 h. The mixture was then washed with deionized water and tetrahydrofuran and centrifuged and dried to obtain SiO2 hollow spheres with PPCM grafted on the outer surface.
[0046] (2) The SiO2 hollow spheres grafted with PPCM on the outer surface were dispersed in ethanol and ultrasonically treated (500W) for 1 h to break them into pieces, thereby obtaining SiO2-PPCM nanosheets;
[0047] (3) 1 g of SiO2-PPCM nanosheets was dispersed in chloroform, and then 5 g of silane coupling agent KH560 was added to react at 40°C for 2 h to graft epoxy groups on its surface, and then 2 g of right-handed polylactic acid PDLA was added and reacted at 80°C in a three-necked flask (nitrogen) for 20 h. Finally, the Janus nanosheets were obtained after sufficient stirring, centrifugation, washing with chloroform, and drying.
[0048] Example 3
[0049] A method for preparing PDLA / PPCM Janus nanosheets comprises the following steps:
[0050] (1) 20 g of PPC was used as a diol and distilled under reduced pressure at 110° C. for 6 h, then cooled to 60° C. The distilled PPC diol was dropped into 6.5 g of lysine diisocyanate, and 0.005 g of dibutyltin dilaurate was added as a catalyst. The reaction was stirred at 60° C. for 5 h under nitrogen conditions; then 250 mL of SiO2 hollow ball dispersion (0.75 / 100, g / mL) and 4 g of curcumin were added, the temperature was lowered to 40° C. and stirred for 18 h; then the mixture was washed with deionized water and tetrahydrofuran and centrifuged and dried to obtain SiO2 hollow balls with PPCM grafted on the outer surface;
[0051] (2) The SiO2 hollow spheres grafted with PPCM on the outer surface were dispersed in ethanol and ultrasonically treated (600W) for 1.5h to break them into pieces, thereby obtaining SiO2-PPCM nanosheets;
[0052] (3) 1 g of SiO2-PPCM nanosheets was dispersed in chloroform, and then 10 g of silane coupling agent KH560 was added and reacted at 50° C. for 3.5 h to graft epoxy groups on its surface. Then 5 g of right-handed polylactic acid PDLA was added and reacted at 100° C. in a three-necked flask (nitrogen) for 25 h. Finally, the Janus nanosheets were obtained after sufficient stirring, centrifugation, washing with chloroform, and drying.
[0053] Application Example 1
[0054] A method for preparing a tough high barrier functional film material comprises the following steps:
[0055] 70 parts of PLLA, 30 parts of PPC, and 0.1 parts of PDLA / PPCM Janus nanosheets prepared in Example 1 were fully dried and premixed in a high-speed mixer according to the weight ratio for 5 minutes, and then put into an extruder for continuous melt extrusion and granulation. The screw temperature was 190°C and the screw speed was 200rpm. The dried pellets were extruded into thin sheets by a screw extruder and quickly cooled to below 15°C. The cooled thin sheets were biaxially stretched using a flat film biaxial stretching process, and then heat treated and cooled to room temperature to obtain a strong and tough high barrier functional film material, wherein the stretching temperature was 70°C, the heat treatment temperature was 100°C, the transverse stretching ratio was 4 times, and the longitudinal stretching ratio was 4 times.
[0056] Application Example 2
[0057] A method for preparing a tough high barrier functional film material comprises the following steps:
[0058] 70 parts of PLLA, 30 parts of PPC, and 0.5 parts of PDLA / PPCM Janus nanosheets prepared in Example 1 were fully dried and premixed in a high-speed mixer according to the weight ratio for 5 minutes, and then put into an extruder for continuous melt extrusion and granulation. The screw temperature was 190°C and the screw speed was 200rpm. The dried pellets were extruded into thin sheets by a screw extruder and quickly cooled to below 15°C. The cooled thin sheets were biaxially stretched using a flat film biaxial stretching process, and then heat treated and cooled to room temperature to obtain a strong and high barrier functional film material, wherein the stretching temperature was 70°C, the heat treatment temperature was 100°C, the transverse stretching ratio was 4 times, and the longitudinal stretching ratio was 4 times.
[0059] Application Example 3
[0060] A method for preparing a tough high barrier functional film material comprises the following steps:
[0061] 70 parts of PLLA, 30 parts of PPC, and 1.5 parts of PDLA / PPCM Janus nanosheets prepared in Example 1 were fully dried and premixed in a high-speed mixer according to weight ratio for 5 minutes, and then put into an extruder for continuous melt extrusion and granulation, with a screw temperature of 190°C and a screw speed of 200rpm. The dried pellets were extruded into thin sheets by a screw extruder and quickly cooled to below 15°C. The cooled thin sheets were biaxially stretched using a flat film biaxial stretching process, and then heat treated and cooled to room temperature to obtain a strong and tough high barrier functional film material, wherein the stretching temperature was 70°C, the heat treatment temperature was 100°C, the transverse stretching ratio was 4 times, and the longitudinal stretching ratio was 4 times.
[0062] Application Example 4
[0063] A method for preparing a tough high barrier functional film material comprises the following steps:
[0064] 70 parts of PLLA, 30 parts of PPC, and 3 parts of PDLA / PPCM Janus nanosheets prepared in Example 1 were fully dried and premixed in a high-speed mixer according to the weight ratio for 5 minutes, and then put into an extruder for continuous melt extrusion and granulation. The screw temperature was 190°C and the screw speed was 200rpm. The dried pellets were extruded into thin sheets by a screw extruder and quickly cooled to below 15°C. The cooled thin sheets were biaxially stretched using a flat film biaxial stretching process, and then heat treated and cooled to room temperature to obtain a strong and tough high barrier functional film material, wherein the stretching temperature was 70°C, the heat treatment temperature was 100°C, the transverse stretching ratio was 4 times, and the longitudinal stretching ratio was 4 times.
[0065] Application Example 5
[0066] A method for preparing a tough high barrier functional film material comprises the following steps:
[0067] 60 parts of PLLA, 40 parts of PPC, and 3 parts of PDLA / PPCM Janus nanosheets prepared in Example 1 were fully dried and premixed in a high-speed mixer according to the weight ratio for 5 minutes, and then put into an extruder for continuous melt extrusion and granulation. The screw temperature was 190°C and the screw speed was 200rpm. The dried pellets were extruded into thin sheets by a screw extruder and quickly cooled to below 15°C. The cooled thin sheets were biaxially stretched using a flat film biaxial stretching process, and then heat treated and cooled to room temperature to obtain a strong and tough high barrier functional film material, wherein the stretching temperature was 70°C, the heat treatment temperature was 100°C, the transverse stretching ratio was 4 times, and the longitudinal stretching ratio was 4 times.
[0068] Application Example 6
[0069] A method for preparing a tough high barrier functional film material comprises the following steps:
[0070] 90 parts of PLLA, 10 parts of PPC, and 3 parts of PDLA / PPCM Janus nanosheets prepared in Example 1 were fully dried and premixed in a high-speed mixer according to weight ratio for 6 minutes, and then put into an extruder for continuous melt extrusion and granulation, with a screw temperature of 200°C and a screw speed of 200rpm. The dried pellets were extruded into thin sheets by a screw extruder and quickly cooled to below 15°C. The cooled thin sheets were biaxially stretched using a flat film biaxial stretching process, and then heat treated and cooled to room temperature to obtain a strong and tough high barrier functional film material, wherein the stretching temperature was 75°C, the heat treatment temperature was 110°C, the transverse stretching ratio was 4 times, and the longitudinal stretching ratio was 4 times.
[0071] Application Example 7
[0072] A method for preparing a tough high barrier functional film material comprises the following steps:
[0073] 70 parts of PLLA, 30 parts of PPC, and 3 parts of PDLA / PPCM Janus nanosheets prepared in Example 2 were fully dried and premixed in a high-speed mixer according to the weight ratio for 5 minutes, and then put into an extruder for continuous melt extrusion and granulation. The screw temperature was 190°C and the screw speed was 200rpm. The dried pellets were extruded into thin sheets by a screw extruder and quickly cooled to below 15°C. The cooled thin sheets were biaxially stretched using a flat film biaxial stretching process, and then heat treated and cooled to room temperature to obtain a strong and tough high barrier functional film material, wherein the stretching temperature was 70°C, the heat treatment temperature was 100°C, the transverse stretching ratio was 4 times, and the longitudinal stretching ratio was 4 times.
[0074] Application Example 8
[0075] A method for preparing a tough high barrier functional film material comprises the following steps:
[0076] 70 parts of PLLA, 30 parts of PPC, and 3 parts of PDLA / PPCM Janus nanosheets prepared in Example 3 were fully dried and premixed in a high-speed mixer according to the weight ratio for 5 minutes, and then put into an extruder for continuous melt extrusion and granulation. The screw temperature was 190°C and the screw speed was 200rpm. The dried pellets were extruded into thin sheets by a screw extruder and quickly cooled to below 15°C. The cooled thin sheets were biaxially stretched using a flat film biaxial stretching process, and then heat treated and cooled to room temperature to obtain a strong and tough high barrier functional film material, wherein the stretching temperature was 70°C, the heat treatment temperature was 100°C, the transverse stretching ratio was 4 times, and the longitudinal stretching ratio was 4 times.
[0077] Application Example 9
[0078] A method for preparing a tough high barrier functional film material comprises the following steps:
[0079] 70 parts of PLLA, 30 parts of PPC, and 3 parts of PDLA / PPCM Janus nanosheets prepared in Example 1 were fully dried and premixed in a high-speed mixer according to the weight ratio for 5 minutes, and then put into an extruder for continuous melt extrusion and granulation. The screw temperature was 190°C and the screw speed was 150rpm. After granulation, the pellets were dried in a vacuum oven. The film was prepared by casting using a casting machine and the film was quickly cooled by cooling water. The screw temperature was 200°C and the screw speed was 200rpm. The above-mentioned tube embryo was inflated and stretched at 70°C at the same time by a tube-film biaxial stretching process, and then heat-treated and cooled to room temperature to obtain a strong and high-barrier functional film material. The heat treatment temperature was 100°C, the blowing ratio was 3 times, and the stretching ratio was 5 times.
[0080] Application Example 10
[0081] A method for preparing a tough high barrier functional film material comprises the following steps:
[0082] 60 parts of PLLA, 40 parts of PPC, and 3 parts of PDLA / PPCM Janus nanosheets prepared in Example 1 were fully dried and premixed in a high-speed mixer according to the weight ratio for 5 minutes, and then put into an extruder for continuous melt extrusion and granulation. The screw temperature was 190°C and the screw speed was 150rpm. After granulation, the pellets were dried in a vacuum oven. A film casting machine was used to prepare a thin film and the thin film was quickly cooled by cooling water. The screw temperature was 200°C and the screw speed was 200rpm. The above-mentioned tube embryo was inflated and stretched at 70°C at the same time by a tube-film biaxial stretching process, and then heat-treated and cooled to room temperature to obtain a strong and high-barrier functional film material. The heat treatment temperature was 100°C, the blowing ratio was 3 times, and the stretching ratio was 5 times.
[0083] Application Example 11
[0084] A method for preparing a tough high barrier functional film material comprises the following steps:
[0085] 90 parts of PLLA, 10 parts of PPC, and 3 parts of PDLA / PPCM Janus nanosheets prepared in Example 1 were fully dried and premixed in a high-speed mixer according to the weight ratio for 6 minutes, and then put into an extruder for continuous melt extrusion and granulation. The screw temperature was 200°C and the screw speed was 150rpm. After granulation, the pellets were dried in a vacuum oven. A film casting machine was used to prepare a thin film and the film was quickly cooled by cooling water. The screw temperature was 200°C and the screw speed was 200rpm. The above-mentioned tube embryo was inflated and stretched at 75°C at the same time by a tube-film biaxial stretching process, and then heat-treated and cooled to room temperature to obtain a strong and high-barrier functional film material. The heat treatment temperature was 110°C, the blowing ratio was 3 times, and the stretching ratio was 5 times.
[0086] Comparative Example 1
[0087] Compared with Application Example 1, PDLA / PPCM Janus nanosheets were not added, and other conditions remained unchanged, as follows:
[0088] 70 parts of PLLA and 30 parts of PPC were fully dried and premixed in a high-speed mixer according to the weight ratio for 5 minutes, and then put into an extruder for continuous melt extrusion and granulation, with a screw temperature of 190°C and a screw speed of 200rpm. The dried pellets were extruded into thin sheets by a screw extruder and quickly cooled to below 15°C. The cooled thin sheets were biaxially stretched using a flat film biaxial stretching process, and then heat treated and cooled to room temperature to obtain a functional film material, wherein the stretching temperature was 70°C, the heat treatment temperature was 100°C, the transverse stretching ratio was 4 times, and the longitudinal stretching ratio was 4 times.
[0089] Comparative Example 2
[0090] Compared with Application Example 1, the number of PDLA / PPCM Janus nanosheets added was changed to 5, and other conditions remained unchanged, as follows:
[0091] 70 parts of PLLA, 30 parts of PPC, and 5 parts of PDLA / PPCM Janus nanosheets prepared in Example 1 were fully dried and premixed in a high-speed mixer according to weight ratio for 5 minutes, and then put into an extruder for continuous melt extrusion and granulation, with a screw temperature of 190°C and a screw speed of 200rpm. The dried pellets were extruded into thin sheets by a screw extruder and quickly cooled to below 15°C. The cooled thin sheets were biaxially stretched using a flat film biaxial stretching process, and then heat treated and cooled to room temperature to obtain a functional film material, wherein the stretching temperature was 70°C, the heat treatment temperature was 100°C, the transverse stretching ratio was 4 times, and the longitudinal stretching ratio was 4 times.
[0092] Comparative Example 3
[0093] Compared with Application Example 1, the number of PLLA added is changed to 50, the number of PPC added is changed to 50, and other conditions remain unchanged, as follows:
[0094] 50 parts of PLLA, 50 parts of PPC, and 0.1 parts of PDLA / PPCM Janus nanosheets prepared in Example 1 were fully dried and premixed in a high-speed mixer according to weight ratio for 5 minutes, and then put into an extruder for continuous melt extrusion and granulation, with a screw temperature of 190°C and a screw speed of 200rpm. The dried pellets were extruded into thin sheets by a screw extruder and quickly cooled to below 15°C. The cooled thin sheets were biaxially stretched using a flat film biaxial stretching process, and then heat treated and cooled to room temperature to obtain a functional film material, wherein the stretching temperature was 70°C, the heat treatment temperature was 100°C, the transverse stretching ratio was 4 times, and the longitudinal stretching ratio was 4 times.
[0095] Comparative Example 4
[0096] Compared with Application Example 5, the number of PDLA / PPCM Janus nanosheets added was changed to 5, and other conditions remained unchanged, as follows:
[0097] 60 parts of PLLA, 40 parts of PPC, and 5 parts of PDLA / PPCM Janus nanosheets prepared in Example 1 were fully dried and premixed in a high-speed mixer according to the weight ratio for 5 minutes, and then put into an extruder for continuous melt extrusion and granulation, with a screw temperature of 190°C and a screw speed of 200rpm. The dried pellets were extruded into thin sheets by a screw extruder and quickly cooled to below 15°C. The cooled thin sheets were biaxially stretched using a flat film biaxial stretching process, and then heat treated and cooled to room temperature to obtain a functional film material, wherein the stretching temperature was 70°C, the heat treatment temperature was 100°C, the transverse stretching ratio was 4 times, and the longitudinal stretching ratio was 4 times.
[0098] Comparative Example 5
[0099] Compared with Application Example 4, the flat film is not biaxially stretched, and other conditions remain unchanged, as follows:
[0100] 70 parts of PLLA, 30 parts of PPC, and 3 parts of PDLA / PPCM Janus nanosheets prepared in Example 1 were fully dried and premixed in a high-speed mixer according to weight ratio for 5 minutes, and then put into an extruder for continuous melt extrusion and granulation, with a screw temperature of 190° C. and a screw speed of 200 rpm. The dried pellets were extruded into sheets by a screw extruder and quickly cooled to below 15° C. to obtain a functional membrane material.
[0101] Comparative Example 6
[0102] Compared with Application Example 9, PDLA / PPCM Janus nanosheets were not added, and other conditions remained unchanged, as follows:
[0103] 70 parts of PLLA and 30 parts of PPC were fully dried and premixed in a high-speed mixer according to the weight ratio for 5 minutes, and then put into the extruder for continuous melt extrusion and granulation. The screw temperature was 190°C and the screw speed was 150rpm. After granulation, the pellets were dried in a vacuum oven. The film was prepared by casting using a casting machine and the film was quickly cooled by cooling water. The screw temperature was 200°C and the screw speed was 200rpm. The above-mentioned tube embryo was inflated and stretched at 70°C by the tube film biaxial stretching process, and then heat treated and cooled to room temperature to obtain a functional membrane material. The heat treatment temperature was 100°C, the blowing ratio was 3 times, and the stretching ratio was 5 times.
[0104] Comparative Example 7
[0105] Compared with Application Example 9, the biaxial stretching of the tubular film is not performed, and other conditions remain unchanged, as follows:
[0106] 70 parts of PLLA, 30 parts of PPC, and 3 parts of PDLA / PPCM Janus nanosheets prepared in Example 1 were fully dried and premixed in a high-speed mixer according to weight ratio for 5 minutes, and then put into an extruder for continuous melt extrusion and granulation, with a screw temperature of 190°C and a screw speed of 150rpm. After granulation, the pellets were dried in a vacuum oven. A film was prepared by casting using a casting machine and the film was quickly cooled by cooling water, with a screw temperature of 200°C and a screw speed of 200rpm, to obtain a functional membrane material.
[0107] Comparative Example 8
[0108] Compared with Application Example 1, PPC, PPCM, PLLA, PDLA, curcumin, and SiO2 hollow microspheres (pure nanosheets without any modification or grafting) were added together, and other conditions remained unchanged, as follows:
[0109] 70 parts of PPC, 30 parts of PLLA, 1 part of PPCM, 1 part of PDLA, 3 parts of curcumin, and 3 parts of SiO2 hollow microspheres were fully dried and premixed in a high-speed mixer according to weight ratio for 5 minutes, and then put into an extruder for continuous melt extrusion and granulation, with a screw temperature of 190°C and a screw speed of 200rpm. The dried pellets were extruded into sheets by a screw extruder and quickly cooled to below 15°C. The cooled sheets were biaxially stretched using a flat film biaxial stretching process, and then heat treated and cooled to room temperature to obtain a functional membrane material, wherein the stretching temperature was 70°C, the heat treatment temperature was 100°C, the transverse stretching ratio was 4 times, and the longitudinal stretching ratio was 4 times.
[0110] After being fully dried, the tough high barrier functional film material obtained in the above application examples 1-11 was tested for tensile properties at room temperature according to the GB / T 1040-2006 standard method. The tensile rate was set to 10 mm / min. At least 5 specimens of the same sample were tested and the average value was taken. The results are shown in Table 1.
[0111] Table 1
[0112] Application Examples Breaking strength(MPa) Elongation at break (%) Application Example 1 138 332 Application Example 2 140 339 Application Example 3 143 344 Application Example 4 146 371 Application Example 5 136 389 Application Example 6 155 299 Application Example 7 145 372 Application Example 8 145 308 Application Example 9 147 332 Application Example 10 137 381 Application Example 11 156 293
[0113] The tough high barrier functional film material obtained in the above application examples 1-11 was fully dried and then tested for oxygen permeability using an oxygen transmission rate tester according to the GB / T 1038 standard method. The test conditions were 20°C, relative humidity 30%, sample thickness 20 μm, and film test area 38.48 cm 2 ; The water vapor transmission rate tester was used to test the moisture permeability of the material according to the GB / T 1037 standard method. The test conditions were 38°C, relative humidity 95%, sample thickness 20μm, and film test area 33cm 2; The sensitivity of the film to NH3 was determined at 90% RH, because packages containing fresh meat generally have higher RH. The UV-vis spectra of the films change with the change of NH3 content. As the NH3 concentration increases, the maximum absorbance value at 420nm continues to decrease, while the absorbance value at 540nm continues to increase. Yellow absorbs light of the wavelength corresponding to its complementary color, blue (~400~480nm), and red absorbs light of the wavelength corresponding to its complementary color, green (~495 570nm). Therefore, the absorbance ratio at 540nm and 420nm (A540 / A420), that is, the wavelength of each complementary color, can indicate the increase of red intensity over yellow intensity, and when the A540 / A420 value is higher, the red is deeper. The A540 / A420 value increases with the increase of NH3 concentration, indicating that the color of the film gradually changes from yellow to red. The calibration fitting curve shows that the A540 / A420 value has a good linear relationship with the NH3 concentration in the range of 0ppm and 300ppm.
[0114] LOD=3K / N
[0115] The detection limit (LOD) of the tough high barrier functional film material for NH3 was determined. K is the standard deviation of the blank measurement (the standard deviation of the A540 / A420 values of the PLLA / PPC blend film without the addition of Janus nanosheets was measured ten times), and N is the slope of the calibration curve. The ultraviolet protection factor (UPF) was calculated from the ultraviolet transmittance in the range of 290nm-400nm. The above results are shown in Table 2.
[0116] Table 2
[0117]
[0118] The functional membrane materials obtained in the above comparative examples 1-8 were tested for their performance qualities using the same testing process. The results are shown in Tables 3 and 4.
[0119] Table 3
[0120] Comparative Example Breaking strength(MPa) Elongation at break (%) Comparative Example 1 79 88 Comparative Example 2 104 102 Comparative Example 3 62 158 Comparative Example 4 65 138 Comparative Example 5 30 149 Comparative Example 6 59 106 Comparative Example 7 31 136 Comparative Example 8 32 67
[0121] Table 4
[0122]
[0123]
[0124] It can be seen from Table 1 and Table 3 that the breaking strength and elongation at break of the blend of polylactic acid and polypropylene carbonate (Comparative Example 1) after adding PDLA / PPCMJanus nanosheets (Application Examples 1-11) are significantly improved compared with direct blending. At this time, the uniform dispersion and volume expansion efficiency of PDLA / PPCM Janus nanosheets are high, so the mechanical properties of the polylactic acid blends, such as breaking strength and elongation at break, are improved. Unmodified SiO2 hollow microspheres and ungrafted curcumin are added in Comparative Example 8, and their various properties are not significantly improved compared with the pure sample. This shows that the compatibility of the two polymers is not good, and the addition of SiO2 hollow microspheres does not play a good volume expansion effect, and the dispersibility is poor. As can be seen from Tables 2 and 4, ungrafted curcumin may agglomerate in the blend, affecting its responsiveness to ammonia. It can be seen from the PLLA / PPC blends with different PDLA / PPCM Janus nanosheet addition contents (Application Examples 1-4) that with the addition of Janus nanosheets, the compatibility is significantly improved, and the mechanical properties of the blends are also significantly improved. However, when the content of PDLA / PPCM Janus nanosheets is too much (Comparative Examples 2, 4), the compatibility and mechanical properties of the blends are somewhat reduced. The reason is that too many nanosheets are accumulated at the interface of the two phases and distributed in the two phases, affecting the mechanical properties of the blends. In addition, the barrier properties of the material are also significantly improved by the double-drawing process (Comparative Examples 5, 7). When the blend is not stretched, its barrier properties are poor. On the other hand, the grafted curcumin of the present invention further improves its functionality, so that its blend film has good UV resistance (Application Examples 1-11) far higher than the excellent level (UPF50+), as well as a lower ammonia detection limit. The stereocomposite crystals formed by the grafted PDLA and the matrix PLLA on the PDLA / PPCM Janus nanosheets further enhance the strength of the polymer blend film (Application Examples 1-11, Comparative Examples 1, 6). In summary, the present invention prepares a tough high-barrier functional film material, which is simple and practical, has high strength, good toughness, good UV resistance and sensitive ammonia detection ability, is easy to industrialize, and is expected to be used in film packaging materials, agricultural greenhouse film materials and other fields.
[0125] The embodiments provided above are not intended to limit the scope of the present invention, and the steps described are not intended to limit the execution order thereof. Those skilled in the art may make obvious improvements to the present invention in combination with existing common knowledge, which also fall within the scope of protection defined by the claims of the present invention.
Claims
1. A tough high barrier functional film material, characterized in that: The method comprises the following raw materials in parts by weight: 60-90 parts of L-polylactic acid, 10-40 parts of polypropylene carbonate, and 0.1-3 parts of PDLA / PPCM Janus nanosheets; PDLA / PPCM Janus nanosheets are made of SiO2 hollow spheres, and poly(propylene carbonate) diol grafted with curcumin and dextrorotatory poly(lactic acid) are modified on both sides of the template, respectively.
2. The tough high barrier functional film material according to claim 1, characterized in that: The preparation method of PDLA / PPCM Janus nanosheets is as follows: (1) PPC diol and lysine diisocyanate are reacted first, and then SiO2 hollow sphere dispersion and curcumin are added to prepare SiO2 hollow spheres with PPCM grafted on the outer surface; (2) The SiO2 hollow spheres with PPCM grafted on the outer surface are crushed to obtain SiO2-PPCM nanosheets, which are then reacted with a silane coupling agent and dextrorotatory polylactic acid to obtain the PDLA / PPCM Janus nanosheets.
3. The tough high barrier functional film material according to claim 2, characterized in that: In step (1), the molar ratio of PPC diol to lysine diisocyanate is 1:2-3.
4. The tough high barrier functional film material according to claim 2, characterized in that: In step (1), the SiO2 hollow sphere dispersion is prepared by dispersing the SiO2 hollow spheres in tetrahydrofuran; the concentration of the SiO2 hollow sphere dispersion is 0.5-0.75 g / 100 mL; and the particle size of the SiO2 hollow spheres is 4.5-5.5 μm.
5. The tough high barrier functional film material according to claim 2, characterized in that: In step (1), the mass volume ratio of PPC diol to SiO2 hollow sphere dispersion liquid is 5-10 / 100, g / mL; the mass volume ratio of curcumin to SiO2 hollow sphere dispersion liquid is 1-5 / 100, g / mL.
6. The tough high barrier functional film material according to claim 2, characterized in that: In step (2), the ultrasonic crushing conditions are: 500-600W ultrasonic treatment for 1-1.5h; The reaction conditions are as follows: SiO2-PPCM nanosheets are dispersed in chloroform, and then a silane coupling agent KH560 is added to react at 40-50°C for 2-3.5 hours to graft epoxy groups on its surface, and then right-handed polylactic acid PDLA is added to react at 80-100°C for 20-25 hours, and finally the Janus nanosheets are obtained after sufficient stirring, centrifugation, washing with chloroform, and drying.
7. The tough high barrier functional film material according to claim 2, characterized in that: In step (2), the silane coupling agent is KH560; the mass ratio of SiO2-PPCM nanosheets, dextrorotatory polylactic acid and silane coupling agent is 1:2-5:5-10.
8. A method for preparing the tough high barrier functional film material according to any one of claims 1 to 7, characterized in that: The steps include: 60-90 parts of L-polylactic acid, 10-40 parts of polypropylene carbonate, and 0.1-3 parts of PDLA / PPCM Janus nanosheets are melt-blended and then molded to obtain the tough high-barrier functional film material.
9. The preparation method according to claim 8, characterized in that: The specific steps are: 60-90 parts of L-polylactic acid, 10-40 parts of polypropylene carbonate, and 0.1-3 parts of PDLA / PPCM Janus nanosheets are blended at 190-200°C for 5-6 minutes, and then extruded to form a film or sheet, and then rapidly cooled to below 15°C to make its crystallinity less than 10%; then the cooled film or sheet is biaxially stretched at 70-75°C using a flat film biaxial stretching process, and then heat treated at 100-110°C to obtain the tough high barrier functional film material; or, 60-90 parts of left-lactic acid, 10-40 parts of polypropylene carbonate, and 0.1-3 parts of PDLA / PPCM Janus nanosheets are blended at 190-200°C for 5-6 minutes, and then formed into a tube embryo through a tube die, and the tube embryo is quickly cooled to below 15°C to make its crystallinity less than 10%; the cooled tube embryo is then inflated, stretched, and shaped at 70-75°C using a tube film biaxial stretching process, and then heat-treated at 100-110°C to obtain the tough high-barrier functional film material.
10. An application of the tough high barrier functional film material according to claim 1, characterized in that: Used in food, daily necessities, environment, agriculture or medicine.
Citation Information
Patent Citations
Surface grafted curcumin modified degradable polyurethane composite material as well as preparation method and application thereof
CN111675820A
Janus nanoparticle, preparation method thereof and bio-based polyester composition prepared from Janus nanoparticle
CN118812863A
Tough transparent polylactic acid two-way stretch film and preparation method thereof
CN118813016A